Adalimumab effectively reduces the signs and symptoms of active ankylosing spondylitis in patients with total spinal ankylosis. Issue 9 (4th December 2007) - van der Heijde, D; Pangan, A L; Schiff, M H; Braun, J; Borofsky, M; Torre, J; Davis, J C; Wong, R L; Kupper, H; Collantes, E; ,
Abstract : Objective: To evaluate the long-term safety and efficacy of adalimumab in patients with ankylosing spondylitis (AS) and total spinal ankylosis (TSA). Design: Patients (n = 315) with active AS were randomised in a 2:1 ratio to receive adalimumab 40 mg every other week or placebo for 24 weeks followed by open-label adalimumab for up to 5 years. Two-year efficacy and safety data for 11 patients with investigator-defined TSA were evaluated. The primary end point was the ASsessment in AS International Working Group criteria for 20% improvement (ASAS20) at Week 12. On or after Week 12, ASAS20 non-responders could switch to open-label adalimumab. Other efficacy measurements included ASAS40, ASAS 5/6, ASAS partial remission, and 50% improvement in the Bath AS Disease Activity Index (BASDAI 50). Results: 6 of 11 TSA patients were randomised to adalimumab and 5 to placebo. At Week 12, 50% of the adalimumab-treated patients achieved an ASAS20 response and 33% achieved an ASAS40, ASAS 5/6 and BASDAI 50. No placebo-treated patients achieved any response criteria at Week 12. 4 placebo- and 2 adalimumab-treated patients switched to open-label adalimumab before Week 24. After 1 year of adalimumab treatment, 8 of 11 patients achieved an ASAS20 response. After 2 years, 6 of the remaining 8 patients with TSA reported an ASAS20 response. There were no serious adverse events or adverse event-related study discontinuations. Conclusion: In patients with TSA, adalimumab treatment resulted in rapid and clinically significant improvement in the signs and symptoms of active disease. Adalimumab effectiveness and safety were sustained for at least 2 years. Trial registration number: NCT00085644.